A Juridical Review of Modern Wound Care Education by Healthcare Professionals Through YouTube in the Perspective of Indonesian Law - Rendy Rahmawan; Happy Yulia Anggraeni (Journal of Law, Politic and Humanities, 2025)
This study investigates the legal status of health education, particularly modern wound care, disseminated through YouTube, as well as the legal protection against misinformation. The findings highlight two main issues. First, YouTube-based health education may be classified as health advocacy; however, under Indonesian law, health advocacy faces normative challenges. Although Law No. 17 of 2023 recognizes health advocacy, it does not clearly regulate the role of non-medical personnel in public health education, creating risks of misleading information in digital spaces. Second, legal protection against misinformation relies primarily on Law No. 1 of 2024 concerning false information, which serves as a lex generalis within health law. This regulation is not sufficiently responsive to health-related misinformation and may conflict with constitutional rights to freedom of expression under Article 28E of the 1945 Constitution. Therefore, a progressive legal paradigm is necessary, emphasizing not only repressive but also preventive measures, such as specific regulations or certification for health content creators. The study concludes that challenges in social media–based health education are not solely medical but also policy-related, requiring the state to balance freedom of expression with the right to health as a fundamental public interest.